Innovation in Islamic Education in the Era of Intelligent Technology: An Ethical and Value-Based Perspective - Amaliah, Nisa; Salim, Hakimuddin (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of intelligent technologies has significantly accelerated innovation in Islamic education. However, such innovation has largely been dominated by a technical-instrumental approach that prioritizes efficiency and system performance, often marginalizing ethical considerations and the normative goals of Islamic education. This study aims to analyze innovation in Islamic education in the era of intelligent technology from an ethical and value-based perspective and to reconstruct an innovation framework aligned with the fundamental objectives of Islamic education. Employing a qualitative approach with a library research design, this study utilizes qualitative content analysis of reputable academic literature on Islamic education, intelligent technology, and educational ethics. The findings reveal that innovation in Islamic education undergoes transformations across pedagogical, institutional–managerial, and epistemological domains, each carrying significant ethical implications for pedagogical relationships, scholarly authority, and educational orientation. As a conceptual contribution, this study proposes an ethical framework for innovation in Islamic education that positions technology as a supportive instrument, human beings as the primary subjects of education, and Islamic values as the normative compass guiding innovation. The study concludes that sustainable innovation in Islamic education must integrate technological advancement with the cultivation of moral character, ethical awareness, and students’ spiritual development.